ROsulord® sAfety for Patients with Dyslipidemia Study: A Non-interventional, Multicenter, Prospective, Observational Study in South Korea - Do Young Kim; Sung Hea Kim; Eung-Ju Kim; Sang-Jin Han; Ji-Yeong Park; Jong-Chan Youn; Hee-Seok Kim; Ji-Eun Jeong; Kyu-Hyung Ryu (Cardiology and Therapy)
Abstract Introduction The ROsulord® sAfety for patients with Dyslipidemia study (ROAD study) in the Republic of Korea investigated the safety and efficacy of rosuvastatin in routine clinical practice. Methods This non-interventional, multicenter, prospective, observational study was conducted over a period of approximately 4.6 years and involved 14,243 participants. During this study, we assessed the adverse events, changes in laboratory test results, and efficacy endpoints associated with rosuvastatin use. Results The findings revealed a notably low adverse event rate of 1.63%, indicating a favorable safety profile for rosuvastatin in the management of dyslipidemia. Importantly, no clinically significant incidences of statin-associated myopathy, hepatotoxicity, or diabetes were observed during the study period. Moreover, this study demonstrated significant improvements in lipid profiles among patients receiving rosuvastatin treatment, with a reduction in total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels. These improvements contributed to a lower cardiovascular risk in the study population. Conclusion Overall, these findings suggest that rosuvastatin is safe and effective in managing dyslipidemia in real-world clinical settings, providing clinicians with valuable insights into the benefits and risks associated with statin therapy in this patient population.